Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan Pada PT Kereta Api Indonesia (Persero) Periode 2019-2023 - Achmadi, Ryan; Manjaleni, Rola (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study examines the financial performance of PT Kereta Api Indonesia (Persero) during the period 2019 to 2023 through a comparative study of three main financial indicators: Current Ratio (CR), Return on Assets (ROA), and Debt to Equity Ratio (DER). This analysis aims to evaluate the company's liquidity, profitability, and capital structure and identify potential risks and opportunities for improvement by referring to industry standards according to Kasmir (2019). The author uses a descriptive qualitative research method in this study. The study conducted in the period 2019 to 2023 examined the results of the financial ratio analysis of PT Kereta Api Indonesia (Persero) showing that the Current Ratio (CR) averaged 1,111.7%, far above the ideal standard of 200%, reflecting very strong liquidity but inefficiency in the use of current assets. Return on Assets (ROA) averaged 6.76%, meeting Kasmir's minimum standard (5%), but still below the optimal level (10%), indicating the potential for less than optimal asset utilization. The average Debt to Equity Ratio (DER) is 162.8%, exceeding Kasmir's safe limit (maximum 100%), indicating high dependence on debt and long-term solvency risk. The study concluded that PT KAI needs to balance liquidity, profitability, and solvency strategies to achieve long-term financial stability. The implications of the analysis results can be a reference for management in formulating operational and financial policies, as well as for stakeholders in assessing the company's investment prospects.